Analysis of the Role of Financial Technology in Enhancing Financial Transparency at Baitul Maal wa Tamwil Fajar Lampung - Mawardi; Ulil Albab; Ajibu Jonas (Nuban Jagadhita Centre, 2026)
Purpose: This study aims to analyze the role of Financial Technology (fintech) in enhancing financial transparency at BMT Fajar Lampung and to identify internal and external factors influencing the effectiveness of its implementation within Islamic financial institutions. Methodology: The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation involving management, financial staff, and BMT members. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing, further strengthened by thematic analysis and triangulation to ensure validity. Findings: The findings reveal that the implementation of fintech plays a significant role in enhancing financial transparency at BMT Fajar Lampung through the digitalization of financial records, real-time reporting, and easier access to financial information. Fintech adoption reduces information asymmetry, improves the efficiency and accuracy of financial management, and strengthens accountability in line with Sharia governance principles. However, its effectiveness is influenced by human resource capacity, managerial commitment, technological infrastructure, and the level of digital literacy. These findings indicate that fintech serves as a strategic tool for promoting transparency, accountability, and institutional trust.